"Life-Steps" for PrEP Adherence: Demonstration of a CBT-Based Intervention to Increase Adherence to Preexposure Prophylaxis (PrEP) Medication Among Sexual-Minority Men at High Risk for HIV Acquisition. Issue 1 (February 2017) - Taylor, S. Wade; Psaros, Christina; Pantalone, David W.; Tinsley, Jake; Elsesser, Steven A.; Mayer, Kenneth H.; Safren, Steven A.
Abstract: One dramatic advance in human immunodeficiency virus (HIV) prevention efforts has been the prescription of medications typically used for HIV treatment as prophylaxis against acquiring HIV. As a preventative agent, this practice is referred to as "preexposure prophylaxis" (PrEP). The U.S. Federal Drug Administration approved daily PrEP for adults at risk for HIV who do not consistently use condoms during sex with HIV-infected or unknown-status partners. In this paper, we describe a cognitive-behavioral therapy (CBT) PrEP adherence intervention developed for use in high-risk sexual-minority men in the United States, adapted from "Life-Steps, " an evidence-based CBT intervention to promote adherence to HIV treatment. Modules include creating a PrEP dosing schedule, adhering to daily PrEP, problem solving barriers to adherence, and sexual risk-reduction techniques. Supplemented with practical video vignettes, this novel intervention may help to enhance the clinical practice of health care providers in outpatient settings to increase PrEP adherence in sexual-minority men. Highlights: An HIV preexposure prophylaxis adherence intervention for sexual-minority men is presented. The intervention draws on Life-Steps and CBT to increase medication adherence. Video vignettes illustrate key aspects of the intervention with a model patient.